The effects of Enterprise Risk Management on the performance and risk of Vietnamese listed firms: Evidence from abnormal Enterprise Risk Management Index - Nguyen Thi Hoa Hong (Global Business & Finance Review (GBFR), 2023)
Purpose: This paper examines the effects of Enterprise Risk Management (ERM), as measured by the Abnormal Enterprise Risk Management Index (ABERMI), on the performance and risk of Vietnamese listed firms. Design/methodology/approach: The paper employs a combination of three regression methods (Pooled Ordinary Least Squares, Fixed Effect Model and Random Effect Model) to test the effects of Enterprise Risk Managment on the performance and risk of Vietnamese listed firms in the period of 2010-2020. In addition, a two-stage regression model is used to calculate the ABERMI. Findings: The findings show that firms with effective enterprise risk management (ERM), as evidenced by their low abnormal enterprise risk management index, can enhance their business performance measured by Tobin's Q. Furthermore, good ERM helps firms reduce the risk of bankruptcy. However, the research proves that ERM is not associated with return on total assets and systematic risk. Research limitations/implications: Firm can employ Enterprise Risk Management (ERM) to efficiently and effectively manage risk. Additionally, applying a standard might further enhance the quality of risk management efforts by managers. Authorities can encourage the implementation of ERM to safeguard investor's wealth and indirectly protect the Vietnamese economy. Originality/value: Through a comprehensive analysis of various methodologies, this paper aims to uncover positive outcomes in exploring the impact of Enterprise Risk Management (ERM) on both risk and performance within the setting of Vietnamese listed firm.
Keywords: 650; Abnormal Enterprise Risk Management Index (ABERMI); Enterprise Risk Management (ERM); firm performance; firm risk; Vietnam